1994
DOI: 10.1161/01.hyp.23.6.982
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic baroreceptor responses after chronic NG-nitro-L-arginine methyl ester treatment in conscious rats.

Abstract: Blood pressure elevations after nitric oxide inhibition may result in part from increased sympathetic tone. In this study arterial baroreceptor reflex control of heart rate, renal sympathetic nerve activity (RSNA), and adrenal sympathetic nerve activity (ASNA) were compared in rats given normal tap water or a 3.7 nmol/L (10 mg%) solution of jV°-nitro-L-arginine methyl ester (L-NAME) for 1 or 5 weeks. L-NAME raised blood pressure after 5 weeks of treatment (153±3 versus 130±3 and 124±2 mm Hg, 5 weeks versus 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…32,33 Although we do not have a good explanation for this, we suspect that eNOS may affect the control of baroreflex resetting 34,35 or be involved in establishing the baroreceptor set point. 36 Another possibility is that nNOS expression might be enhanced in eNOS knockout mice as a compensatory mechanism. Increased nNOS activity may have a direct effect on cholinergic receptors and decrease heart rate, because a link between cholinergic receptor stimulation and NOS activation has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Although we do not have a good explanation for this, we suspect that eNOS may affect the control of baroreflex resetting 34,35 or be involved in establishing the baroreceptor set point. 36 Another possibility is that nNOS expression might be enhanced in eNOS knockout mice as a compensatory mechanism. Increased nNOS activity may have a direct effect on cholinergic receptors and decrease heart rate, because a link between cholinergic receptor stimulation and NOS activation has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic eNOSKO mice serum aldosterone levels tended to be lower than that in wild-type diabetic mice, likely because NO deficiency is associated with impairment of sympathetic nervous system. 18,19 However, in contrast, serum aldosterone tended to be paradoxically increased with RAS blockade in eNOSKO mice ( Figure 4H). Mineralocorticoid receptor expression was induced by the diabetic condition in both wild-type and eNOSKO mice ( Table 2).…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 93%
“…75 These effects may be partly mediated via a reduction in sensitivity of the baroreceptor reflex, which contributes permissively to L-NAME hypertension. 76 In contrast, other investigators have reported evidence that renal nerve traffic plays little or no role in the hypertension of chronic NOS inhibition. 77 The relationship between NO and the SNS is likely to be highly complex, with direct interactions at the various adrenergic receptor subtypes and indirect interactions through baroreceptor control of BP, for example, providing numerous and sometimes opposing influences.…”
Section: Role Of the Cns And The Snsmentioning
confidence: 95%